Landasan Yuridis Tentang Pengesahan Perjanjian Mutual Legal Assistance antara Republik Indonesia dengan Konfederasi Swiss - Miarsa, Fajar Rachmad Dwi; Hazir, Cholilla Adhaningrum (Lembaga Layanan Pendidikan Tinggi Wilayah XII, 2021)
The intensity of criminal acts committed across countries, with crimes and modus operandi that are difficult to identify. This raises problems that require juridical countermeasures by engaging in intense cooperation between countries. The study has the goal of (1) to find out and explain the legal basis behind the reciprocated legal aid in criminal problems between Indonesia - Swiss, and (2) to study about a form of mutual legal assistance between Republic of Indonesia with Confederacy of Swiss. The method of research used was normative juridical research, known in law science as normative law research. The legal material in this study is primary material and secondary material. The analysis technique used is a descriptive method of describing an event that was thoroughly studied and providing legal arguments on the subject. Under law about International treaties, it is a regulation that provides a legal basis for Indonesian governments in requesting or providing mutual legal assistance in criminal matters (under article 2 of act about mutual legal assistance) the agreement between Indonesia with Swiss is explained in article 2 of treaty on mutual legal assistance in criminal matters between the republic of Indonesia and the Swiss Confederation.